Biomass determination, growth response and light use efficiency of mid-rotation Pinus radiata stands, post thinning - Pienaar, Louis Otto (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhDFor)--Stellenbosch University, 2025.